Creating Relationship Bonds: An Exploration of Brand Resonance Research - SASTRINA, Tia; GIANTARI, I Gst. Ayu Kt.; SETIAWAN, Putu Yudi; SUASANA, I Gst. A. Kt. Gd. (Journal of Entrepreneurial and Business Diversity, 2024)
Purpose: Brand resonance is essential for organizations to understand as they seek to build stronger relationships with the public. Brands are expected to understand what drives the relationship between consumers and their brand and take steps to build brand resonance.Methodology:This article was prepared using the literature study research method by collecting data from other scientific works such as journals, international journals, and proceedings that discuss matters related to brand resonance, perceived value, brand experience, brand love, and social media marketing through stages of data collection and categorization of data from journals and paper proceedings related to brand resonance, perceived value, brand experience, brand love, and social media marketing.Findings: Brand resonance is the highest relationship that can be successfully built between a brand and its consumers in the form of behavioral Loyalty, attitudinal attachment, sense of community, and active engagement.Implication:In this literature review, several factors influence brand resonance between consumers and a brand: perceived value, brand experience, brand love, and social media marketing.